Red seaweed extracts reduce methane production by altering rumen fermentation and microbial composition in vitro - Choi, Youyoung; Lee, Shin Ja; Kim, Hyun Sang; Eom, Jun Sik; Jo, Seong Uk; Guan, Le Luo; Park, Tansol; Seo, Jakyeom; Lee, Yookyung; Bae, Dongryeoul; Lee, Sung Sill (Frontiers in Veterinary Science, 2022)
A series of in vitro batch culture incubations was carried out to investigate changes in rumen fermentation characteristics, methane (CH4) production, and microbial composition in response to supplementation with five different red seaweed species (Amphiroa anceps, AANC; Asparagopsis taxiformis, ATAX; Chondracanthus tenellus, CTEN; Grateloupia elliptica, GELL; and Gracilaria parvispora, GPAR). Prior to the incubations, the total flavonoid and polyphenol content of the red seaweed extracts was quantified. The incubated substrate consisted of timothy hay and corn grain (60:40 dry matter (DM) basis). Treatments were substrate mixtures without seaweed extract (CON) or substrate mixtures supplemented with 0.25 mg/mL of red seaweed extract. Samples were incubated for 6, 12, 24, 36, and 48 h. Each sample was incubated in triplicates in 3 separate runs. In vitro DM degradability, fermentation parameters (i.e., pH, volatile fatty acids, and ammonia nitrogen), total gas production, and CH4 production were analyzed for all time points. Microbial composition was analyzed using 16S rRNA amplicon sequencing after 24 h of incubation. The highest CH4 reduction (mL/g DM, mL/g digested DM, and % of total gas production) was observed in ATAX (51.3, 50.1, and 51.5%, respectively, compared to CON; P < 0.001) after 12 h of incubation. The other red seaweed extracts reduced the CH4 production (mL/g DM; P < 0.001) in the range of 4.6–35.0% compared to CON after 24 h of incubation. After 24 h of incubation, supplementation with red seaweed extracts tended to increase the molar proportion of propionate (P = 0.057), and decreased the acetate to propionate ratio (P = 0.033) compared to the CON. Abundances of the genus Methanobrevibacter and total methanogens were reduced (P = 0.050 and P = 0.016) by red seaweed extract supplementation. The linear discriminant analysis effect size (P < 0.05, LDA ≥ 2.0) showed that UG Succinivibrionaceae, Anaeroplasma, and UG Ruminococcaceae, which are associated with higher propionate production, starch degradation, and amylase activity were relatively more abundant in red seaweed extracts than in the CON. Our results suggest that supplementation with red seaweed extracts altered the microbiota, leading to the acceleration of propionate production and reduction in CH4 production.